Prevalence of Antibiotic Residues and Antibiotic Resistance in Isolates of Chicken Meat in Korea - Lee, Hyo-Ju (Korean J Food Sci Anim Resour, 2018)
The aim of study was to investigate the correlation between the level of 17 antibiotic residues and 6 antibiotic resistances of Escherichia coli isolates in chicken meats. A total of 58 chicken meats were collected from retail grocery stores in five provinces in Korea. The total detection rate of antibiotic residues was 45% (26 out of 58). Ten out of 17 antibiotics were detected in chicken meats. None of the antibiotics exceeded the maximum residue level (MRLs) in chicken established by the Ministry of Food and Drug Safety (MFDS). The most detected antibiotics were amoxicillin (15.5%), followed by enrofloxacin (12.1%) and sulfamethoxazole (10.3%). In a total of 58 chicken meats, 51 E. coli strains were isolated. E. coli isolates showed the highest resistance to ampicillin (75%), followed by tetracycline (69%), ciprofloxacin (65%), trimethoprim/ sulfamethoxazole (41%), ceftiofur (22%), and amoxicillin/clavulanic acid (12%). The results of study showed basic information on relationship between antibiotic residue and resistance for 6 compounds in 13 chicken samples. Further investigation on the antibiotic resistance patterns of various bacteria species is needed to improve food safety.